THE IMPLEMENTATION OF SIMPLE ADDITIVE WEIGHTING METHOD IN THE SELECTION OF REHABILITATION FUND RECIPIENTS FOR UNINHABITABLE HOME - Krisbiantoro, Dwi; Baihaqi, Wiga Maulana (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2019)
The rehabilitation program is one of the programs given to people who have homes that are not habitable. They are usually from poor families with low economic income. In this program, the family will receive funds to rehabilitate their home. However, as long as the program is running, various problems have been encountered, including those who received fund sometimes received back the fund for rehabilitation funds. This is of course not in accordance with regulations that only allow applicants to receive the fund once. Based on this problem, a decision support system was made to select potential recipients of rehabilitation funds for uninhabitable house. By using the SAW method which is based on the value of criteria and preference weights, an appropriate assessment and ranking can be obtained after going through the selection process of assessing the weight of each attribute. The support for the selection decision for receiving uninhabitable rehabilitation fund was generated in this study. Decision making to determine beneficiaries was facilitated by the existence of a decision support system that was submitted, so that the fund provided was targeted at those entitled to receive uninhabitable rehabilitation fund.